French translation and validation of the Cumberland Ankle Instability Tool, an instrument for measuring functional ankle instability. Issue 4 (June 2020) - Geerinck, A.; Beaudart, C.; Salvan, Q.; Van Beveren, J.; D'Hooghe, P.; Bruyère, O.; Kaux, J.-F.
Highlights: The Cumberland Ankle Instability Tool is now available in French. The CAIT-F is a reliable tool for detecting and rating functional ankle instability. A score of ≤23 points indicates the presence of functional ankle instability. Abstract: Background: Ankle sprains are one of the most common musculoskeletal injuries, and can lead to chronic ankle instability (CAI). The Cumberland Ankle Instability Tool (CAIT) measures a subset of CAI, functional ankle instability (FAI). Because no French version existed, we set out to translate and validate the CAIT in French. Methods: The CAIT was translated using a forward-backward methodology. We examined its psychometric properties and calculated a cut-off score for FAI in a sample of 102 subjects (median age 22 years). Results: The CAIT was translated without significant problems. The CAIT-F can discriminate between those with and without FAI (p < 0.001), with a cut-off score of ≤ 23 points. The test-retest reliability is excellent (ICC = 0.960), as is the internal consistency (α = 0.885). Construct validity was confirmed. No floor or ceiling effects were detected among subjects with FAI. Conclusions: The CAIT is now available in French, and is a valid and reliable instrument.